Penerapan Metode Technology Acceptance Model untuk Pengukuran Tingkat Penerimaan Aplikasi SIM3LON - Adila Safitri; Ni’mah Akbar Habibie; Illyin Almeito; Moh. Hasyimi; Yonathan Saputra; Eko Sediyono; Aris Puji Widodo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
This research was conducted to test user acceptance (agent and base) of SIM3LON system using Technology Acceptance Model (TAM). This test was done by measuring the influence of variable Perceived Ease of Use, Perceived Usefulness and Intention to use with a likert value of 1-5 with TAM method. The testing method is done using the R GUI tool to generate validity and reliability values and perform calculations using the